Oliver Mtukudzi’s Pindirai (intervene): A call for environmental sustainability in Zimbabwe - Chitando, Anna; Madongonda, Angeline M. (Journal for Studies in Humanities and Social Sciences, 2015)
The theme of environmental degradation has emerged as a major concern to activists, politicians, academics and others. Of late, musicians have also sought to contribute to the struggle for environmental conservation. This is because music plays multiple roles in society. It critiques issues such as abuse of power, gender imbalances and the exploitation of the environment. This article utilises Oliver Mtukudzi’s song, “Pindirai” to examine its contribution towards environmental sustainability in Zimbabwe. Employing Huggan and Tiffin’s postcolonial ecocriticism (2010), the article utilises textual analysis of Mtukudzi’s song to identify themes that promote environmental sustainability. Loosely defined, pindirai means (intervene). The article, therefore, investigates Mtukudzi’s role as an artist in an endeavour to establish his authority in calling upon his compatriots to become sensitive and friendly to the environment. While appreciating Mtukudzi’s artistic creativity and commitment to environmental sustainability, the article interrogates the assumptions behind the portrayal of Zimbabweans as engaging in ecologically harmful behaviour. It suggests the need to tackle deeper questions relating to survival in order to promote environmental sustainability. In turn, this would ensure sustainable development.